Long-term conservation agriculture improves water-nutrient-energy nexus in maize-wheat-greengram system of South Asia - Ghosh, Sonaka; Das, T. K.; Raj, Rishi; Sudhishri, Susama; Mishra, A. K.; Biswas, Dipak Ranjan; Bandyopadhyay, K. K.; Ghosh, Sourav; Susha, V. S.; Roy, Arkaprava; Alekhya, Gunturi; Saha, Priyanka; et al. (Frontiers in Sustainable Food Systems, 2025)
Contemporary crop management practices are labor, water, and energy inefficient. Identifying a sustainable, productive, and resource-efficient alternate crop production system to the present crop management system is crucial. A field experiment was conducted to assess the effects of conservation agriculture (CA) on crop growth, productivity, and resource use efficiency under the maize-wheat-greengram system during 9th (2018–19) and 10th (2019–20) years of the study. CA-based bed planting methods such as permanent narrow, broad and flat beds with and without retention of crops residues and 75% and 100% of the recommended dose of nitrogen (N) were compared with conventional tillage (CT) treatment. The permanent broad bed with residue with 100% recommended dose of N (PBB + R + 100N) resulted in 56.0%, 60.0% and 26.5% higher root length density in maize, wheat, and greengram crops, respectively. The PBB + R + 100N registered 31.1% higher system productivity than CT. The partial factor productivity (PFP) of N, P, and K were higher under PBB + R + 75N. The CA-based broad-bed practices registered 10.2 and 18.1% savings of irrigation water application than narrow-bed and flat-bed with residue retention, respectively. The CA-based practices without residue retention obtained significantly higher energy productivity, net energy return, and energy ratio than CT. Adopting the CA practice involving a permanent broad bed with residue using 100% N (PBB + R + 100N) in a maize-wheat-greengram system would be more productive and efficient for nutrients, water, and energy. This study focuses on the potential of CA to improve nutrient, water, and energy security in the maize-wheat-greengram system in South Asia.